Integration and the Diplomatic Crisis: Current Realities of the GCC - L. V. Shkvarya (Vestnik MGIMO-Universiteta)
The article analyzes the integration process in the Gulf Cooperation Council group countries (GCC), which was founded in 1981. Regional economic integration in the GCC has passed through the several traditional stages: the Free trade zone, the Customs Union and the Common market. Certain exceptions remain in the GCC integration, but the countries aim to create a full economic Union by 2025. Currently, the GCC is one of the most advanced and successful integration associations in developing countries. However, the GCC is the only truly functioning integration bloc in the MENA region. The author's analysis confirms that the share of intraregional trade is growing in the GCC, but this share is less high than in other integration blocs. The author emphasizes that the GCC countries have significant success in the world market of goods and capital. The GCC trade turnover is growing steadily, although it depends on fluctuations in world oil prices. The GCC region attracts a lot of foreign investment and technology. This allows them to continue to diversify their national economies. The level and quality of life in the GCC is improving. These and other achievements are largely the result of regional economic integration and cooperation between countries in various areas on the world and regional markets. At the same time, the GCC is one of the most strategically important regions in the world economy and politics. Economic and political processes are influenced by many factors, both internal and external. Therefore, there are many contradictions in the GCC, and sometimes crisis situations are formed. One of them is the current "diplomatic crisis". It began in 2017 and has so far created numerous problems in the region and in the Arab world as a whole. It also has a negative impact on the development and deepening of integration processes. The author analyzed statistical data for 2009-2018 and justified the conclusion that the "diplomatic crisis" damages intraregional trade, reduces the dynamics of macroeconomic indicators, and worsens the position of the GCC countries in the world market of goods and capital. It also creates difficulties for citizens of GCC countries and companies that operate in the region. Now GCC countries should develop a mechanism to de-escalate the crisis, as this is in the economic and political interests of all participants and the Middle East as a whole. The relevance of the research is due to the need to analyze regional economic integration processes in the subregion in the context of growing global instability. The research makes a significant contribution to understanding the nature and features of integration processes in the Middle East.